Study of Illumination Optical System to Control Light Pollution due to Night Lighting - Sun Yoo, Kyung; Young Lee, Soo; Hoon Hyun, Dong; Jo Jung, Byoung (International Journal of Engineering and Technology, 2018)
Background/Objectives: Artificial light has developed with both sides of light pollution. International organizations recognize the seriousness of light pollution and are offering ways to make restrictions light pollution.Methods/Statistical analysis: It padded an additional surface on the back of the lens to convert the light to the House side into a street side. The slope of the additional surface was determined by the angle of the light that emerged from the LED.As a result, it implemented B1 rating of security light on BUG Rating defined by IESNA.Findings: The total internal reflection of the lens was used to control the posterior light. The inner surface was set to totally reflect the light directed toward the house side inside the lens, and the inclination of the outer surface was set so that the light refracted from the outer surface and directed forward when the light exits. As a result of controlling the backlight in this way, the B1 light distribution classified by the BUG rating was implemented. It also made the ratio of light from Street side to House side about 8:2.Improvements/Applications: When applying the expression proposed in this paper to the streetlight optical system, it can complement the light pollution problem.Â Â